Gambling involvement and problem gambling correlates among European adolescents: results from the European Network for Addictive Behavior study - Andrie, E.K.; Tzavara, C.K.; Tzavela, E.; Richardson, C.; Greydanus, D.; Tsolia, M.; Tsitsika, A.K. (2019)
Purpose: Worldwide, concern has grown over the expansion of gambling among adolescents, who have an increased likelihood of developing risk-taking behaviors. This study aimed to increase knowledge of problem gambling among adolescents in seven European countries and to assess the effect of demographic and lifestyle factors recorded in the European Network for Addictive Behavior survey (https://www.eunetadb.eu). Methods: A cross-sectional school-based study (n = 13,284) was conducted in Germany, Greece, Iceland, The Netherlands, Poland, Romania and Spain. Anonymous self-completed questionnaires included socio-demographic data, internet usage characteristics, school achievement, parental control, the Internet Addiction Test, the South Oaks Gambling Screen-Revised for Adolescents Test and Achenbach’s Youth Self-Report. Results: 12.5% of the participants reported last year gambling activities either online or offline. 3.6% of the study participants and 28.1% of gamblers (either online or offline) were at risk or had a gambling problem. The study results showed that a higher proportion of adolescents was either at risk or had a gambling problem among males, in the older age group, when the parental educational level was lower/middle, and in the absence of siblings. Furthermore, being at risk or having a gambling problem was associated with lower age at first use of the internet, lower school grades, using the internet 6–7 days per week, and problematic internet use. At risk or problem gamblers had higher scores on all scales of problem behavior and lower scores (lower competence) on activities and academic performance. Conclusions: Our findings underline the need for better gambling legislation and suggest the importance of developing social responsibility tools that may help diminish adolescent gambling involvement, with special attention to males. © 2019, Springer-Verlag GmbH Germany, part of Springer Nature.